Genetic Diversity and Population Structure of the critically endangered freshwater fish species, the Clanwilliam sandfish (Labeo seeberi) - Lesch, Shaun Francois (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.